2013
DOI: 10.1111/liv.12209
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological characteristics of hepatocellular carcinoma in Egypt: a retrospective analysis of 1313 cases

Abstract: HCC is a major health problem in Egypt and its incidence is increasing. The high prevalence of HCV infection makes screening programmes and surveillance of those patients a very important tool to early detect cases of small HCCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 31 publications
(40 reference statements)
5
32
0
1
Order By: Relevance
“…Similar results were presented by Shaker et al [16] who showed that 38.6% of their cohort had more than one hepatic focal lesion. Vascular invasion was found in 23.5% in our HCC patients.…”
Section: Discussionsupporting
confidence: 78%
“…Similar results were presented by Shaker et al [16] who showed that 38.6% of their cohort had more than one hepatic focal lesion. Vascular invasion was found in 23.5% in our HCC patients.…”
Section: Discussionsupporting
confidence: 78%
“…It is well known, in addition, that HCV infection is associated with HCC carcinogenesis, especially in the Egyptian population (24). Hence it is important to further detect the potential association between HCV-induced cirrhosis and these biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…In Egypt, HCC is a major health problem and its incidence is increasing being related to high incidence of HCV [31]. HCC constitutes 70.48% of all liver tumors among Egyptians and represents the main complication of cirrhosis with about 21% of cirrhotic patients at risk of developing HCC [32,33].…”
Section: Hepatocellular Carcinoma (Hcc)mentioning
confidence: 99%